Principles of Optogenetic Methods and Their Application to Cardiac Experimental Systems - Ferenczi, Emily A.; Tan, Xiaoqiu; Huang, Christopher L.-H. (Frontiers in Physiology, 2019)
Optogenetic techniques permit studies of excitable tissue through genetically-expressed light-gated microbial channels or pumps permitting transmembrane ion movement. Light activation of these proteins modulates cellular excitability with millisecond precision. This review summarizes optogenetic approaches, using examples from neurobiological applications, then explores their application in cardiac electrophysiology. We review the available opsins, including depolarizing and hyperpolarizing variants, as well as modulators of G-protein coupled intracellular signaling. We discuss the biophysical properties that determine the ability of microbial opsins to evoke reliable, precise stimulation or silencing of electrophysiological activity. We also review spectrally-shifted variants offering possibilities for enhanced depth of tissue penetration, combinatorial stimulation for targeting different cell subpopulations, or all-optical read-in and read-out studies. Expression of the chosen optogenetic tool in the cardiac cell of interest then requires, at the single-cell level, introduction of opsin-encoding genes by viral transduction, or coupling “spark cells” to primary cardiomyocytes or a stem-cell derived counterpart. At the systems-level, this requires construction of transgenic mice expressing ChR2 in their cardiomyocytes, or in vivo injection (myocardial or systemic) of adenoviral expression systems. Light delivery, by laser or LED, with widespread or multipoint illumination, although relatively straightforward in vitro may be technically challenged by cardiac motion and light-scattering in biological tissue. Physiological read outs from cardiac optogenetic stimulation include single cell patch clamp recordings, multi-unit microarray recordings from cell monolayers or slices, and electrical recordings from isolated Langendorff perfused hearts. Optical readouts of specific cellular events, including ion transients, voltage changes or activity in biochemical signaling cascades, using small detecting molecules or genetically-encoded sensors now offer powerful opportunities for all-optical control and monitoring of cellular activity. Use of optogenetics has expanded in cardiac physiology, mainly using optically-controlled depolarizing ion channels to control heart rate and for optogenetic defibrillation. ChR2-expressing cardiomyocytes show normal baseline and active excitable membrane and Ca2+ signaling properties and are sensitive even to ~1 ms light pulses. They have been employed in studies of the intrinsic cardiac adrenergic system, and of cardiac arrhythmic properties.